Steer gains on burned and nonburned bluestem pasture, 1978 to 1982 - E.F. Smith; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1983)
From 1978 to 1982, steers on a late spring burned pasture averaged 40 lbs more gain each summer than steers on a non-burned pasture.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Gain; Steer; Bluestem